STOXX Europe 600 index: Corporate debt maturity analysis - Magalhães, Jorge Augusto Barreiros (2015)
This dissertation consists of an empirical study about corporate debt maturity structure in STOXX EUROPE 600’ firms. The observation period dates from year 2000 to 2013. Balance sheet yearly observations were used to build firm specific variables (determinants) to use in the model. Through different techniques of regression analysis we assess the changes in the relevance of the determinants in explaining debt maturity by model and throughout the sample period with particular focus to the periods before and after the 2008 subprime crisis. A complementary study on Euro Area yield curve AAA volatility also provides plausible evidence to support main conclusions. The results suggest an optimized structure trend of debt into firm’s balance sheet. A flat amount of debt remains since 2008 but, short-term debt has been replaced by long-term debt, thereby causing an increase of the debt maturity ratio. The specific purpose analysis to Euro Area Yield curve AAA revealed that shorter time interest rates had their volatility in highest levels after the subprime crisis, making riskier for firms to finance themselves using short-term strategies, suggesting this fact to be one plausible cause for the preference for long-term debt. Liquidity determinant dramatically lost his significance after the subprime crisis, while Growth Options determinant increased his. The results also suggested that debt maturity decision is not driven only by firm specific factors, i.e. macro-economic factors also contribute to impact debt maturity, but in a more significant way after the 2008 subprime crisis than before.